Cost-effective hybrid filter for remediation of water from fluoride. Issue 1 (July 2020) - Alhendal, Mohammed; Nasir, Mohsin Jasim; Hashim, Khalid S.; Amoako-Attah, Joseph; Al-Faluji, Duaa; Muradov, Magomed; Kot, Patryk; Abdulhadi, Bareq
Abstract: Incidence of fluoride concentrations in drinking water above the allowable limit (1.5 mg/L) leads to varied health issues. However, fluoride concentration below 1.5 mg/L in drinking water is useful for teeth and bones health. A considerable concentration of fluoride is naturally released to the sources of freshwaters from the geological environment, specifically the groundwater, because of the weathering and seepage of water phenomena influences. Unfortunately, nowadays world population depend on groundwater as the main drinking water source, which means those people are exposed to fluoride contaminations. As a result, contamination of groundwater with fluoride has been lately considered as a universal grave issue. Although fluoride could be removed from drinking water using efficient methods, such as reverse osmosis and filtrations, there is a challenge to develop a cost-effective practical removal method. This study examines the efficiency of an economically-efficient a hybrid filtration cell (HFC), which utilizes limestone and activated carbons, for fluorides removal from water. Batch flow experiments were conducted using HFC to remediate artificial water from fluorides. Additionally, the influences of initial pH, initial concentration of fluoride (IFC), water temperature (WT) and adsorbent dosage (AD) were optimized, using Box–Behnken approach, to reach the highest removal of fluorides. The results demonstrated that fluoride could be completely removed from artificial water when the HFC is run at pH of 5.0, IFC of 30 mg/L, AD of 30 mg/L and WT of 313 K.